2017
DOI: 10.4038/sljfa.v3i1.41
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activities and starch digestion rate of the organically- and non-organically grown traditional rice varieties in Sri Lanka

Abstract: Abstract:The study was designed to assess the total phenolic content (TPC), free radical scavenging activity, antimicrobial property and in vitro starch digestion rate of three traditional rice varieties grown organically and non-organically in Sri Lanka. The 70% ethanol extractions of rice were subjected to TPC, DPPH -free radical scavenging assays to determine antioxidant activity, and antimicrobial susceptible test against three bacteria, namely, Escherichia coli, Salmonella typhi and Staphylococcus aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, these values were significantly higher for non-organically produced Madathawalu seeds which showed 3.83±0.3 for Salmonella typhi and 5.73±0.2 for Staphylococcus aureus. However, both organically and nonorganically produced Madathawalu seed samples had not shown an anti-microbial effect on Escherichia coli [25].…”
Section: Madathawalumentioning
confidence: 83%
See 3 more Smart Citations
“…However, these values were significantly higher for non-organically produced Madathawalu seeds which showed 3.83±0.3 for Salmonella typhi and 5.73±0.2 for Staphylococcus aureus. However, both organically and nonorganically produced Madathawalu seed samples had not shown an anti-microbial effect on Escherichia coli [25].…”
Section: Madathawalumentioning
confidence: 83%
“…Further, they found that organically grown Madathawalu has a high total phenolic content (2.22±0.03 mg gallic acid equivalent/g of rice extract) also compared to the non-organically produced sample (1.42±0.01 mg ascorbic acid equivalent/g of rice extract). The red pericarp rice varieties used in their study (Madathawalu and Handiran) showed higher antioxidant values than the tested white pericarp variety which is Suwandel [25].…”
Section: Madathawalumentioning
confidence: 83%
See 2 more Smart Citations